Crystal structure of 5, 6‐bis(9H‐carbazol‐9‐yl)benzo[c][1, 2, 5]thiadiazole: distortion from a hypothetical higher‐symmetry structure. Issue 4 (7th March 2017) - Averkiev, Boris B.; Davydenko, Iryna; Wang, Xu; Barlow, Stephen; Marder, Seth R.
Abstract : The crystal structures of 5, 6‐bis(9 H ‐carbazol‐9‐yl)benzo[ c ][1, 2, 5]thiadiazole (DCBT) and its hydrate were investigated using single‐crystal X‐ray analysis. The analysis of the crystal packing of DCBT revealed that the experimental triclinic structure could be described as a distortion from a hypothetical higher‐symmetry monoclinic structure. The quantum chemical calculations of two possible monoclinic structures showed that the proposed structures are higher in energy by 5.4 and 10.1 kcal mol −1 . Abstract : Nucleophilic substitution of F atoms in 5, 6‐difluorobenzo[ c ][1, 2, 5]thiadiazole (DFBT) for carbazole could be potentially interesting as a novel way of synthesizing building blocks for new conjugated materials for applications in organic chemistry. The crystal structures of 5, 6‐bis(9 H ‐carbazol‐9‐yl)benzo[ c ][1, 2, 5]thiadiazole (DCBT), C30 H18 N4 S, and its hydrate, C30 H18 N4 S·0.125H2 O, were investigated using single‐crystal X‐ray analysis. The hydrate contains two symmetry‐independent DCBT molecules. The dihedral angles between the plane of the central benzothiadiazole fragment and that of the carbazole units vary between 50.8 and 69.9°, indicating conformational flexibility of the DCBT molecule in the crystals, which is consistent with quantum chemical calculations. The analysis of the crystal packing of DCBT revealed that the experimental triclinic structure could be described as a distortion from a hypothetical higher‐symmetry monoclinic structure. The quantum chemical calculations of two possible monoclinic structures, which are related to the experimental structure by a shifting of molecular layers, showed that the proposed structures are higher in energy by 5.4 and 10.1 kcal mol −1 . This energy increase is caused by less dense crystal packings of the symmetric structures, which results in a decrease of the number of intermolecular interactions.